Design and development of paddy straw bale shredder - S, KUMAR; B, DOGRA; S, MANES G (The Indian Journal of Agricultural Sciences, 2021)
A tractor operated paddy straw bale shredder cum mulcher was designed and developed at Punjab Agricultural University, Ludhiana during 2018-19 to use baled paddy straw as mulch. Mulching reduces weed emergence, increases available water capacity and improves soil properties that results in yield increment. Paddy straw size is generally more than row to row and plant to plant spacing of vegetable crops. Its size was reduced using developed machine. Theoretical design of the machine was followed by development of 3D model and fabrication. The developed machine comprised a shredding rotor for shredding paddy straw bales, a bale drum to handle the bales, a concave grate to control the feeding of bales, a deflector unit for uniform spreading of shredded paddy straw bales and power transmission unit. It has overall dimensions of 1800×1300×1400 mm. The developed machine was run in lab to select operational parameters of the machine. It was further evaluated for mat thickness and uniformity of spread. Effect of forward speed and rotor speed was significant on mat thickness as well as uniformity of spread at 5% level of significance. However, effect of deflector angle on both dependent parameters was non-significant. Mat thickness decreased with increase in forward speed and decrease in rotor speed. Its maximum value was 64 mm for forward speed of 2.7 km/h, rotor speed of 30.7 m/s and deflector angle of 25°. Uniformity of spread was determined using coefficient of variation and its minimum value was 34.38% for forward speed of 2.7 km/h, rotor speed of 30.7 m/s and deflector angle of 25°.